Are US inflation expectations re-anchored? - Dieter Nautz; Till Strohsal (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
Anchored inflation expectations are of key importance for monetary policy. If long-terminflation expectations arewell-anchored, they should be unaffected by short-term economic news. This letter introduces newsregressions with multiple endogenous breaks to investigate the de- and re-anchoring of US inflation expectations. We confirm earlier evidence on the de-anchoring of expectations driven by the outbreak of the crisis. Our results indicate that expectations have not been re-anchored ever since.
Keywords: E31; E52; E58; C22; 330; Anchoring of Inflation Expectations; Break-Even Inflation Rates; News-Regressions; Multiple Structural Break Tests